An Unusual Cause of Ear Pain. A Life Threatening Disease Revealed by a Common Symptom. Issue 6 (November 2016) - Sierecki, M; Marchetti, M; Verdier, M; Ghazali, A
A 40-year-old woman presented to the emergency department (ED) for bilateral otalgia as her sole complaint. The physician's otoscopic examination was normal and the rest of the examination was unremarkable except for previously unknown high blood pressure. The patient had no chest pain or dyspnea. She was discharged from the ED with antihypertensive therapy, pain-relief medications, and an appointment with a cardiologist. Twelve days later, transthoracic echocardiography revealed pericardial effusion and dilated ascending aorta. Computed tomography scan finally diagnosed an aortic dissection (AD) type A (Stanford classification) which necessitated emergency surgery.